Chloride ion erosion resistant concrete and preparation method thereof

By using coal gangue and plastic to replace gravel in concrete and adding calcined clay, the problems of resource waste and chloride ion erosion in the existing technology are solved, and efficient and environmentally friendly concrete preparation is achieved, with good mechanical properties and chloride ion resistance.

CN119707364APending Publication Date: 2025-03-28ANHUI POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411671804.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing concrete preparation technology cannot effectively utilize waste coal gangue and plastics, resulting in waste of resources and environmental pollution, and it is difficult to solve the problem of chloride ion erosion.

Method used

By replacing part of the gravel with coal gangue and plastic, a concrete that resists chloride ion erosion is prepared, with a maximum replacement ratio of 100%, and calcined clay is added to the concrete to improve compressive strength and chloride ion permeability.

Benefits of technology

It achieves high mechanical strength and good anti-chlorine ion penetration properties of concrete, reduces the use of natural gravel, saves resource and environmental pollution, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707364A_ABST
    Figure CN119707364A_ABST
Patent Text Reader

Abstract

According to the chloride ion corrosion resistant concrete and the preparation method thereof, the coal gangue and the plastic are adopted to replace part of the broken stone, the maximum replacement proportion can reach 100%, and due to the fact that the coal gangue and the plastic are waste, the preparation cost of the concrete can be saved; environmental pollution caused by accumulation of a large amount of coal gangue and non-degradable plastic can be reduced, and meanwhile, the environmental problem caused by over-exploitation of gravel can be effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete preparation, and in particular to concrete resistant to chloride ion corrosion and a preparation method thereof. Background Art

[0002] With the rapid development of the global economy and the continuous growth of population, the demand for concrete materials in the construction industry is increasing day by day. In recent years, my country's demand for sand and gravel has reached 15 billion tons / year, with an output value of up to 2 trillion yuan. However, the process of mining sand and gravel will cause great environmental pollution and damage the topography. The environmental restoration work after mining is relatively difficult, and the production areas of sand and gravel are relatively concentrated, and the transportation cost is relatively high. With the rapid development of the global economy and the continuous growth of population, the demand for concrete materials in the construction industry is increasing day by day, and it is also facing the dual pressure of resource shortage and environmental pollution. Therefore, the development of new environmentally friendly, efficient and sustainable building materials has become an urgent need for the industry. Coal gangue is one of the largest industrial solid wastes in my country, and as a waste product of coal mining, its quantity has been increasing and accumulated in large quantities in recent years. The large accumulation of coal gangue not only seriously occupies land and affects land use, but also causes serious pollution to the environment. If it can be processed and prepared into concrete aggregate, it can not only alleviate environmental pollution, but also make up for the shortage of natural sand and gravel resources. In addition, my country is the world's largest producer and consumer of plastics, and the output of waste plastics in my country has been increasing significantly in recent years, but the utilization rate of plastics in my country is low, and it is mainly treated by incineration and landfill, which not only causes serious pollution to the ecological environment, but also a great waste of resources. Foreign countries have studied the use of recycled plastics as a new type of aggregate in concrete. Under appropriate proportions, the mechanical strength of concrete is close to that of the comparison sample, which can not only reduce white pollution, but also produce better economic benefits. At present, the solution to the above problem is generally to add the above materials to the preparation of concrete, and the preparation of such concrete generally uses coal gangue as a raw material for preparation. For example, the disclosed patent 2016103525797 discloses a method for producing concrete channel prefabricated parts using coal gangue, which uses coal gangue as a raw material for concrete production, but does not use plastic as a raw material for production, and cannot solve the current problem of excessive plastic waste. Summary of the invention

[0003] The purpose of the present invention is to provide concrete resistant to chloride ion corrosion and a preparation method thereof. By using coal gangue and plastic to replace part of the crushed stone, the maximum replacement ratio can reach 100%. Since coal gangue and plastic are wastes, not only can the preparation cost of concrete be saved, but also the environmental pollution caused by the large accumulation of coal gangue and non-degradable plastics can be reduced, and at the same time, the environmental problems caused by excessive exploitation of sand and gravel can be effectively prevented.

[0004] The invention provides concrete resistant to chloride ion corrosion. The concrete comprises cement, calcined clay, coal gangue, plastic, crushed stone, common river sand, a water reducing agent and water. The weight of the materials contained in each cubic meter of concrete is as follows: 250-350 kg of cement, 30-100 kg of calcined clay, 150-2000 kg of coal gangue, 50-90 kg of plastic, 0-900 kg of crushed stone, 500-1000 kg of common river sand and 1-10 kg of the water reducing agent.

[0005] A further improvement is that the water-binder ratio of the concrete is w / b=0.54, where the water-binder ratio is the ratio of the mass of water divided by the sum of the mass of cement and calcined clay.

[0006] A further improvement is that each cubic meter of concrete contains the following materials by weight: 315 kg of cement, 46 kg of calcined clay, 176.1-1056.6 kg of coal gangue, 54.7 kg of plastic, 880 kg of crushed stone, 605 kg of ordinary river sand and 2.38 kg of water reducing agent.

[0007] A further improvement is that the cement is ordinary Portland cement with 5-20% mineral admixture, C 3 S+C 2 S≥70%, C 3 S≥50%, specific surface area 320-340 m 2 / kg, 3d compressive strength ≥17 MPa, 3d flexural strength ≥3.5 MPa, 28d compressive strength ≥42.5 MPa, 28d flexural strength ≥6.5 Mpa.

[0008] The further improvement is that the calcined clay is prepared by calcining kaolinite clay ore at 650-800 ° C for 2-3 h and grinding it with a ball mill for 3-6 h. The kaolinite content in the clay ore is 60-75%, the quartz content is ≤25%, the average particle size of the calcined clay is 0.6-1.2 μm, and the specific surface area is 20000-24000 m 2 / kg; activity index 1.1-1.2.

[0009] A further improvement is that the water reducing agent is a liquid polyhydroxy acid-based high-performance water reducing agent with a solid content of 40-50% and a water reduction rate of 25-45%.

[0010] Further improvements are: the ordinary river sand fineness modulus is 2.2, and the particle size is less than 3 mm; the crushed stone is ordinary concrete crushed stone, and the particle size is 5-30 mm; the coal gangue is crushed coal gangue with a hardness close to that of crushed stone, and the particle size is 5-30 mm; the plastic particles are crushed PET plastic bottle bodies, and the particle size is 5-16 mm.

[0011] The compressive strength of the concrete of the present invention at 28 days of age exceeds 30 MPa, the splitting tensile strength reaches above 2.7 MPa, the electric flux after curing for 28 days is less than 2000 C, and the migration coefficient is less than 20×10 -12 m 2 / s, which can effectively prevent chloride ion corrosion of steel bars in concrete components. At the same time, compared with conventional concrete materials, the amount of natural stone used is greatly reduced. 3 Concrete can save up to 1 ton of natural stone and is one of the important means of recycling waste coal gangue and PET plastic.

[0012] The present invention also provides a method for preparing chloride ion resistant concrete, the preparation method comprising the following steps: Step 1: Turn on the mixer power and the agitator switch, and let the mixing barrel start to rotate; Step 2: After the mixing barrel rotates for 10-20 seconds, open the feed port and add the weighed gravel, sand, plastic particles, coal gangue, cement, calcined clay, and stir for 2-3 minutes to fully mix the aggregate and ash; Step 3: Dissolve the water reducer in water, then add water to the feed port and stir for 3-5 minutes to allow the aggregate and cementitious material to fully bond; Step 4: Open the unloading door and unload the mixed concrete; Step 5: Place the stirred mixture into a test mold and vibrate to compact it; Step 6: Seal and cure the prepared concrete specimens together with the mold in a 20 ℃ environment for 24 h, then demold them, and then place them in a constant temperature and humidity curing box at 20 ℃ and 95% humidity for 28 days.

[0013] Compared with conventional concrete, the concrete raw materials prepared by the present invention use gangue and plastic to replace part of the crushed stone, and the maximum replacement ratio can reach 100%. Since gangue and plastic are waste, it can not only save the preparation cost of concrete, but also reduce the environmental pollution caused by the large accumulation of gangue and non-degradable plastics, and at the same time effectively prevent the environmental problems caused by excessive mining of sand and gravel. In addition, the addition of calcined clay reduces the use of cement by 10%, and the carbon emissions of concrete are further reduced. At the same time, the calcined clay in the raw materials reacts with the hydration product of cement, calcium hydroxide, to generate additional hydration products, which improves the compressive strength, splitting tensile strength and chloride ion impermeability of concrete. The mix ratio of concrete in the present invention is a key technology.

[0014] Beneficial effects of the present invention: The concrete material has obvious advantages in terms of economy and environmental protection, and has good mechanical strength and resistance to chloride ion penetration. The 28-day compressive strength exceeds 30 MPa, and the splitting tensile strength exceeds 2.7 MPa, which can meet the strength requirements of C30 concrete. Compared with conventional concrete materials, it has the following two advantages: An effective method for recycling waste coal gangue and plastic in concrete is proposed. The invented concrete has obvious advantages in energy saving and environmental protection.

[0015] First, the natural crushed stone in concrete is mostly open-pit mining, which will have a great impact on the environment around the mining site. Gangue and PET plastic particles are used to replace natural crushed stone, which reduces the demand for crushed stone. Secondly, gangue is the waste generated in the coal mining process. A large amount of gangue accumulation will affect the use of land resources. If it is improperly stored, the heavy metals and acidic substances such as chromium, lead, mercury contained in gangue will penetrate into the land and groundwater, causing great damage to the environment. At the same time, my country is also the world's largest plastic production and consumption country, and plastic production is still growing, but plastics are mostly non-degradable and have a low recovery rate. Burning plastics will produce harmful gases, and piling up and occupying land, solving the plastic problem is urgent. Therefore, in the present invention, gangue and plastic are used to replace crushed stone to prepare concrete, which can effectively solve the problem of gangue accumulation and PET waste plastic treatment, not only responding to the call of national energy conservation and emission reduction, environmental protection, but also saving costs.

[0016] The invented concrete material is low in price and has good mechanical strength and resistance to chloride ion corrosion.

[0017] The calcined clay used in the present invention is a low-carbon, environmentally friendly, and highly active mineral admixture. After the calcined clay is combined with coal gangue and plastic, the compressive strength of the concrete can reach C30 grade, and its splitting tensile strength exceeds 2.6 MPa. The chloride ion flux of the concrete is less than 2000 C, and the chloride ion migration coefficient is less than 20×10 -12 m 2 / s, which can make the concrete have excellent resistance to chloride ion penetration, thereby effectively preventing the steel bars in the concrete components from rusting. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0019] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. Example

[0020] The present embodiment provides concrete resistant to chloride ion corrosion, the concrete comprising cement, calcined clay, coal gangue, plastic, crushed stone, ordinary river sand and water reducing agent, and each cubic meter of concrete comprises the following materials by weight: 315 kg of cement, 46 kg of calcined clay, 176.1 kg of coal gangue, 54.7 kg of plastic, 880 kg of crushed stone, 605 kg of ordinary river sand, 193.5 kg of water and 2.38 kg of water reducing agent.

[0021] In this embodiment, the gravel replacement rate reaches 25%. Example

[0022] The present embodiment provides concrete resistant to chloride ion corrosion, the concrete comprising cement, calcined clay, coal gangue, plastic, crushed stone, ordinary river sand and water reducing agent, and each cubic meter of concrete comprises the following materials by weight: 315 kg of cement, 46 kg of calcined clay, 469.6 kg of coal gangue, 54.7 kg of plastic, 587 kg of crushed stone, 605 kg of ordinary river sand, 193.5 kg of water and 2.38 kg of water reducing agent.

[0023] In this embodiment, the gravel replacement rate reaches 50%. Example

[0024] The present embodiment provides concrete resistant to chloride ion corrosion, the concrete comprising cement, calcined clay, coal gangue, plastic, crushed stone, ordinary river sand and water reducing agent, and each cubic meter of concrete comprises the following materials by weight: 315 kg of cement, 46 kg of calcined clay, 763.1 kg of coal gangue, 54.7 kg of plastic, 294 kg of crushed stone, 605 kg of ordinary river sand, 193.5 kg of water and 2.38 kg of water reducing agent.

[0025] In this embodiment, the gravel replacement rate reaches 75%. Example

[0026] The present embodiment provides concrete resistant to chloride ion corrosion, the concrete comprising cement, calcined clay, coal gangue, plastic, crushed stone, ordinary river sand and water reducing agent, and each cubic meter of concrete contains the following materials by weight: 315 kg of cement, 46 kg of calcined clay, 1056.6 kg of coal gangue, 54.7 kg of plastic, 605 kg of ordinary river sand, 193.5 kg of water and 2.38 kg of water reducing agent.

[0027] In this embodiment, the gravel replacement rate reaches 100%. In order to verify the chloride ion penetration resistance of the patented concrete material of the present invention, the concrete test blocks that were cured to 28 days of age were subjected to electric flux tests and chloride ion migration coefficient tests in accordance with GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The results are shown in the following table. As shown in Table 3, the electric flux of the concrete test blocks of the present invention at 28 days is less than 2000C, and the chloride ion migration coefficient is less than 20×10 -12 m 2 / s [1] According to JGJ / T 193-2009 "Concrete Durability Test and Evaluation Standard", this concrete belongs to QⅢ grade concrete and has good resistance to chloride ion penetration, which can effectively prevent chloride ions from corroding the steel bars in concrete components.

[0028] like Figure 1 As shown, the above four groups of embodiments use the following preparation method, which comprises the following steps: Step 1: Turn on the mixer power and the agitator switch, and let the mixing barrel start to rotate; Step 2: After the mixing barrel rotates for 10-20 seconds, open the feed port and add the weighed gravel, sand, plastic particles, coal gangue, cement, calcined clay, and stir for 2-3 minutes to fully mix the aggregate and ash; Step 3: Dissolve the water reducer in water, then add water to the feed port and stir for 3-5 minutes to allow the aggregate and cementitious material to fully bond; Step 4: Open the unloading door and unload the mixed concrete; Step 5: Place the stirred mixture into a test mold and vibrate to compact it; Step 6: Seal and cure the prepared concrete specimens together with the mold in a 20 ℃ environment for 24 h, then demold them, and then place them in a constant temperature and humidity curing box at 20 ℃ and 95% humidity for 28 days.

Claims

1. A chloride ion resistant concrete, characterized in that: The concrete comprises cement, calcined clay, coal gangue, plastic, crushed stone, ordinary river sand, water reducing agent and water. The weight of the above materials contained in each cubic meter of concrete is: 250-350 kg of cement, 30-100 kg of calcined clay, 150-2000 kg of coal gangue, 50-90 kg of plastic, 0-900 kg of crushed stone, 500-1000 kg of ordinary river sand and 1-10 kg of water reducing agent.

2. The chloride ion resistant concrete according to claim 1, characterized in that: The water-cement ratio of the concrete is w / b=0.

54.

3. The chloride ion resistant concrete according to claim 1, characterized in that: Each cubic meter of concrete contains the following materials: 315 kg of cement, 46 kg of calcined clay, 176.1-1056.6 kg of coal gangue, 54.7 kg of plastic, 0-880 kg of crushed stone, 605 kg of ordinary river sand and 2.38 kg of water reducing agent.

4. The chloride ion resistant concrete according to claim 1, characterized in that: The cement is ordinary Portland cement with 5-20% mineral admixture, C3S+C2S≥70%, C3S≥50%, and specific surface area of ​​320-340 m 2 / kg, 3d compressive strength ≥17 MPa, 3d flexural strength ≥3.5 MPa, 28d compressive strength ≥42.5 MPa, 28d flexural strength ≥6.5 Mpa.

5. The chloride ion resistant concrete according to claim 1, characterized in that: The calcined clay is prepared by calcining kaolinite clay ore at 650-800°C for 2-3 hours and grinding it with a ball mill for 3-6 hours. The kaolinite content in the clay ore is 60-75%, the quartz content is ≤25%, the average particle size of the calcined clay is 0.6-1.2 μm, and the specific surface area is 20000-24000m 2 / kg; Activity index 1.1-1.

2.

6. The chloride ion resistant concrete according to claim 1, characterized in that: The water reducing agent is a liquid polyhydroxy acid-based high-performance water reducing agent with a solid content of 40-50% and a water reduction rate of 25-45%.

7. The chloride ion resistant concrete according to claim 1, characterized in that: The ordinary river sand has a fineness modulus of 2.2 and a particle size of <3 mm; the crushed stone is ordinary concrete crushed stone with a particle size of 5 to 30 mm; the coal gangue is crushed coal gangue with a hardness close to that of crushed stone, with a particle size of 5 to 30 mm; the plastic particles are crushed PET plastic bottle bodies, with a particle size of 5 to 16 mm.

8. A method for preparing chloride ion resistant concrete according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Step 1: Turn on the mixer power and the agitator switch, and let the mixing barrel start to rotate; Step 2: After the mixing barrel rotates for 10-20 seconds, open the feed port and add the weighed gravel, sand, plastic particles, coal gangue, cement, calcined clay, and stir for 2-3 minutes to fully mix the aggregate and ash; Step 3: Dissolve the water reducer in water, then add water to the feed port and stir for 3-5 minutes to allow the aggregate and cementitious material to fully bond; Step 4: Open the unloading door and unload the mixed concrete; Step 5: Place the stirred mixture into a test mold and vibrate to compact it; Step 6: Seal and cure the prepared concrete specimens together with the mold in a 20 ℃ environment for 24 h, then demold them, and then place them in a constant temperature and humidity curing box at 20 ℃ and 95% humidity for 28 days.